Chemical sensing in development and function of intestinal lymphocytes. (February 2018) - Cervantes-Barragan, Luisa; Colonna, Marco
Highlights: AHR senses environmental cues that modulate intestinal immune cells. AHR is activated by a vast array of exogenous and endogenous ligands. AHR signaling impacts immune cell types like innate lymphoid cells, T and B cells. AHR signaling outcome depends on the specific ligand and cell type involved. Abstract : The immune system of the intestinal tract has the challenging task of recognizing and eliminating intestinal pathogens while maintaining tolerance to dietary and commensal antigens; therefore, it must be able to sense environmental cues within the intestine and mount suitable responses dictated by their pathogenic or nonpathogenic nature. The aryl hydrocarbon receptor (AHR) was originally characterized as a chemical sensor of the environmental pollutant 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin (TCDD) [12 ]. More recently, AHR has emerged as a major chemical sensor expressed in many intestinal immune cells that enables them to distinguish nutritional and microbial cues and is, therefore, important for development, maintenance and function of the intestinal immune system. In this review, we will highlight recent advances in our knowledge of the role of AHR signaling in intestinal innate lymphoid cells (ILC), T cells and B cells.